THE EFFECT of SYNTAGMATIC AND PARADIGMATIC RELATIONSHIP ON LEARNING GRAMMAR AMONG IRANIAN PRE-INTERMEDIATE EFL LEARNERS - Ehsan Namaziandost; Fariba Rahimi Esfahani; Akbar Khajehpour (State Islamic University of North Sumatra Indonesia, 2018)
The purpose of the present study was to explore the effects of using syntagmatic and paradigmatic relationships on learning grammar among Iranian pre-intermediate EFL learners. To fulfill the objectives of the study a Homogeneity test (Oxford Quick Placement Test) was administered among 70 students at the pre-intermediate level of a private language Institute and finally 40 participants were selected. Then, they were randomly divided into two subgroups, namely control and experimental groups. Before starting the treatment, a validated teacher-made grammar test was administered to students as pre-test to assess the participants' knowledge of grammar at the beginning of the course. Then, the experimental group received the treatment, which was teaching grammar through using syntagmatic and paradigmatic relations while the control group was taught using traditional methods of teaching. After 20 sessions of treatment,the two groups were administered the same teacher-made grammar test as post-test. Data were analyzed by Paired and Independent Samples t-test. The findings showed that the experimental group significantly performed better than the control group. Generally, the experimental groups outperformed the control groups. The results suggest that syntagmatic and paradigmatic relations can be used in English classes to develop listening grammar ability among Iranian EFL learners.